Towards a better risk management in companies - KERRAOUS , El mehdi (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Nowadays, risk exerts a significant effect on companies. Its frequency as well as its gravity have drastically increased. Consequently, risk management becomes an absolute necessity for every company. Nevertheless, in many companies risk management is limited to a silo approach where risks are managed individually by traditional tools. However, this approach showed important weaknesses, which resulted in the emergence of a more structured approach of risk management, commonly referred to as “enterprise risk management (ERM)”. This process and its principal contributions are still poorly understood in many companies. This article aims to analyze the weaknesses of a silo-based risk management approach and to clarify ERM and its main contributions. We hope that this article will contribute to the promotion of a true culture of risks within the companies.